ANALISIS KESULITAN SISWA SEKOLAH DASAR DI KOTA SEMARANG PADA PENYELESAIAN SOAL CERITA PEMECAHAN MASALAH MATEMATIKA - Wardana, M yusuf Setia; Subekti, Ervina Eka; Cahyadi, Fajar Cahyadi (Universitas PGRI Semarang, 2021)
The focus of this study was to analyze the difficulties of elementary school students in the city of Semarang in solving math problem solving in terms of Polya's steps. This research is included in qualitative research. This research was conducted in four elementary schools in the city of Semarang, including SD N Jomlang 3 Semarang, SD Negeri Karangtempel Semarang, SD N Gayamsari 2 Semarang and SD N Bugangan 2 Semarang. This study concluded that the percentage of implementing planning was the most difficult problem for students to understand, while 56.38% was followed by planning problems, namely 54.07%, while the difficulty of concluding / checking back was 56.38%, and The difficulty in understanding the problem is the difficulty in the last sequence, which is 44.54.